KALIFERSITE, A NEW ALKALINE SILICATE FROM KOLA PENINSULA (RUSSIA) BASED ON A PALYGORSKITE-SEPIOLITE POLYSOMATIC SERIES - Ferraris G.; Belluso E.; Khomyakov A.P.; Soboleva S.V. (My University, 1998)
Kalifersite, (K, Na)5(Fe3+)7[Si20O50](OH)6 · 12H2O, is a new [001] fibrous silicate discovered in a drill core of a hydrothermally altered pegmatite in the urtite series at Mt. Kukisvumchorr (Kola Peninsula). The new mineral formed by crystallization from residual peralkaline liquids during the hydrothermal stage of the pegmatitic process. Pink-brownish; good {100} and {010} cleavages; D(meas) = 2.37(2) g/cm3. Biaxal (+); α = 1.523(2), β = 1.525(2), γ = 1.550(2), 2V(meas) = 30(2)°, 2V(calc) = 32°; optically pseudo-orthorhombic, O.P. (010); slightly pleochroic. SAED patterns show triclinic symmetry and streaks; a = 14.86(4), b = 20.54(4), c = 5.29(2) Å, α = 95.6(3), β = 92.3(3), γ = 94.4(3)°have been obtained from least-squares refinement of powder diffraction data; s.g. P1̄, Z = 1. Comparison with sepiolite {Mg8[Si12O30](OH)4 · 12H2O; a = 13.40, b = 26.80, c = 5.28 Å, s.g. Pncn, Z = 2} and palygorskite {Mg5[Si8O20](OH)2 · 8H2O; a = 13.27, b = 17.868, c = 5.279 Å, β = 107.38°, s.g. C2/m, Z = 2} allowed to obtain for kalifersite a structural model which explains its characteristics. On the basis of P = [(Y2+)(5-y'-z')(Y3+)(y')[](z')][Si8O20](OH)2{(A(n+))((2z'-y')/n) · m'H2O} (palygorskite module) and S = [(Y2+)(8-y-z)(Y3+)(y)[](z)][Si12O30](OH)4{(A(n+))((2z-y)/n) · mH2O} (sepiolite module), kalifersite is the P(l)S(l) member (with y + y' = 7, z + z' = 6 and m + m' = 12) of a P(p)S(s) polysomatic series named palysepiole series. In kalifersite, the alkali cations A lie in octahedra which connect the Y-octahedra belonging to the palygorskite/sepiolite framework. This feature and polysomatic aspects are discussed by comparison with biopyriboles, raite and, in general, 2:1 layer silicates.